Association between Traditional Mongolian Medicine Body Constitutions and Stroke: A Population based Cross-Sectional Survey in the Tongliao area - Rong, Wang Xiao; Namsrai, Oyuntsetseg; Chaolu, Erdun; Bayarmagnai, Narantuya (Central Asian Journal of Medical Sciences, 2024)
Objectives: This study aims to explore the relationship between body constitution types and risk factors for stroke. Methods: The survey collected demographic data and assessed body constitution according to principles of traditional Mongolian medicine. It included results from physical examinations, laboratory tests, and stroke risk assessment. Additionally, expert evaluations of body types were integrated into the analysis. Results: The study involved 2,086 participants, examining factors associated with stroke through multivariable method. Age was identified as a significant predictor, with stroke risk increasing in individuals aged 60–69 and 70 above, corresponding to adjusted odds ratios (aORs) of 4.56 (P=0.001) and 5.97 (P<0.001), respectively. Male participants were found to have a significantly higher risk of stroke, with an aOR of 1.54 (P=0.014) compared to females. The prevalence of stroke from single body type was 21.2%, 17.6%, and 14.6% for people of type C, A, and B, respectively. Other significant risk factors for stroke included smoking, family history of stroke, hypertension, dyslipidemia, and related comorbidities, all associated with higher aORs. Conclusion: These findings highlight the critical role of demographic, constitutional, and health-related factors in assessing stroke risk in this population. The inclusion of biochemical markers further underscores the need for comprehensive evaluations in stroke prevention strategies.